-5(x-1)=3x+1-4x

Simple and best practice solution for -5(x-1)=3x+1-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(x-1)=3x+1-4x equation:


Simplifying
-5(x + -1) = 3x + 1 + -4x

Reorder the terms:
-5(-1 + x) = 3x + 1 + -4x
(-1 * -5 + x * -5) = 3x + 1 + -4x
(5 + -5x) = 3x + 1 + -4x

Reorder the terms:
5 + -5x = 1 + 3x + -4x

Combine like terms: 3x + -4x = -1x
5 + -5x = 1 + -1x

Solving
5 + -5x = 1 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
5 + -5x + x = 1 + -1x + x

Combine like terms: -5x + x = -4x
5 + -4x = 1 + -1x + x

Combine like terms: -1x + x = 0
5 + -4x = 1 + 0
5 + -4x = 1

Add '-5' to each side of the equation.
5 + -5 + -4x = 1 + -5

Combine like terms: 5 + -5 = 0
0 + -4x = 1 + -5
-4x = 1 + -5

Combine like terms: 1 + -5 = -4
-4x = -4

Divide each side by '-4'.
x = 1

Simplifying
x = 1

See similar equations:

| 32+90+x=180 | | 5/9(-13-32) | | 2x^3+4x^2+4x=-5 | | 4x-32+5x+45=36 | | 2-5m+7=8+2m | | 2x^3+4x^2+4x+5=0 | | 4x-2x=4x-2 | | x^6=14 | | y^2-2x^2=-32 | | 6(4y+3)+(-37y)= | | 0.2x+0.4=-0.6 | | 6(x+2)=5-x | | -7X+74-7(X-1)=9X-(5X-2)-3X+4 | | (1)/(2sin(2x)) | | 5v+3v=64 | | v/4-2.3=-8.7 | | 5=2/3(2x-1) | | -5(x+7)+7=-28 | | (10x+20)+(32+6x)=180 | | 2e+5=e+8 | | U^2+6U+8= | | y-4=1/3(x-3) | | -91=61w+-15w+-19 | | 3n+1=28 | | 3(x+4)=26 | | 91=6w-15w-19 | | x(x+6)=9x^2+3 | | 3/-2x=2/3x-13 | | 8=2x-6/4 | | 6=2u+42+2u | | 10-4abs(3x+2)=0 | | =-16x^2+27x-10 |

Equations solver categories